Simulation of Furfural and Levulinic Acid Production from Lignocellulosic Biomass - Panjaitan, Jabosar Ronggur Hamonangan (Jurnal Teknik Kimia dan Lingkungan, 2023)
Furfural and levulinic acid are chemicals that can be produced from lignocellulosic biomass. In this research, mass balance simulation of furfural and levulinic acid production at scale of 100 tons of biomass/year was examined. This research using various models of kinetic reaction and biomass to solvent ratio from lignocellulosic biomass raw materials consisting of cellulose, hemicellulose, lignin, ash, and water composition of 35%, 30%, 25%, 3%, and 7%. The kinetic models used in this research were separate kinetic models and simultaneous model (model-3). The separate kinetic models were divided into two models which separate kinetic model 1 (model-1) and separate kinetic model 2 (model-2). SuperPro Designer 9.0 software was used to calculate mass balance simulation. From the research, it was found that variations in kinetic reaction model affected furfural and levulinic acid production. Higher biomass to solvent ratio produced higher furfural and levulinic acid production. The highest furfural produced from simulation process was kinetic reaction model-2 with a biomass to solvent ratio of 1:30 and 0.67 liter furfural/hour. While the highest levulinic acid produced from the simulation process was kinetic reaction model-1 with a biomass to solvent ratio of 1:30 and 2.37 liter levulinic acid/hour.